Social issues in sport communication you make the call - Rentner, Terry L.; Burns, David P.
"Combining theory with practical application, this collection of real-life, provocative case studies on social issues in sports provides students with the opportunity to make the call on ethical and professional dilemmas faced by a variety of sport and communication professionals. The case studies examine the successes and failures of communication in the corporate culture of sport intersecting with social issues including race, gender, religion, social media, mass media, public health, and LGBTQ+ issues. Topics include the COVID-19 pandemic, the Black Lives Matter movement, sexual abuse scandals, domestic violence, cultural appropriation, and mental health. Each chapter contextualizes a specific issue, presents relevant theory and practical communication principles, and leads into discussion questions to prompt critical reflection. The book encourages students to view the evidence themselves, consider competing ethical and professional claims, and formulate practical responses. This collection serves as a scholarly text for courses in sport communication, business, intercultural communication, public relations, journalism, media studies, and sport management"--Provided by publisher.
Sport and social issues : the touchdowns and strikeouts / Terry L. Rentner -- "The Rooney ruse" : systemic racism and hiring NFL head coaches / David P. Burns & Chris B. Geyerman -- When fandom stains your team : evaluating the effectiveness of the Utah Jazz's organizational responses to racist incidents / Nicola A. Corbin & Anne Bialowas -- Concussion settlement and racial norming : the NFL fumbles into a crisis / Cory Young, Terry Rentner & Annemarie Farrell -- Major League Soccer's navigation of the 2019 iron front crisis / Caleb Bills -- Protecting the Brees brand : how Drew Brees said "sorry" for his national anthem protest comments / Steph Doehler -- 'Kicking hate out of our game' : San Diego Loyal Soccer Club's stand against racism and homophobia / Jeffrey W. Kassing, Isaiah D. Utley & Steffanie M. Kiourkas -- Issues and crisis management in athlete activism : Colin Kaepernick and take a knee / Lillian Feder -- Reputation management strategies at ESPN / Kevin Hull & Denetra Walker -- From Les Esquimaux to The Elks : addressing social responsibility in the Canadian Football League / David J. Jackson & Lori Liggett -- In the space of indecision : social and cultural challenges facing Major League Soccer NEXT Academies / Saleema Mustafa Campbell & Erin E. Gilles -- #WeAreAllMonkeys : eating bananas as the intersection of hashtag activism and anti-racist solidarity / Pratik Nyaupane -- The Milwaukee Bucks : professional athletic labor's position in racist late-stage capitalism / Kevin Thompson -- Conquering a boy's club using an issues management approach : how women's soccer may pioneer a path to pay equity / Terry L. Rentner & David P. Burns -- Communicating in crisis without the power to act / Bradley J. Baker -- Strategic resistance through communication capital : Rapinoe's reframing of women-identified athletes through mind-body performance for social change / Elesha L. Ruminski & Dorene Ciletti -- Alysia, Allyson, and Nike's 'and of Brothers' : exposing the hypocrisy between corporate marketing and internal practices / Amy Aldridge Sanford, Nikola Grafnetterova & RJ Loa -- Let them wear shorts! : analyzing the Norwegian women's beach handball team's uniform code protest / Megan R. Hill, Karen T. Erlandson, & Katey A. Price -- Sports news media, major leagues, and intimate partner violence / Steve Ingham, Jade Metzger-Riftkin & Tara McManus -- 'Play like the lady you are' : marketing women's Gaelic football / Niamh Kitching -- Trans inclusion in sports : assumed advantages, (un)fairness, and athlete well-being / Aaron W. Gurlly -- Athlete influence in regard to mask wearing : an application of social cognitive theory / Lindsey J. DiTirro & Jennifer R. Allen Catellier -- Controlling the narrative : NBC, USA Gymnastics, and Simone Biles at the 2020 Summer Olympic Games / Aaron W. Gurlly -- "We hope to see you soon" : the Green Bay Packers crisis management through a letter to the fans during COVID-19 mega-crisis / Julia C. Richmond -- Blaming Biles : intersectionality and organizational obligations to mental health / Jeff Nagel & Scott J. Varda -- How can organizations better support athletes? : a case study of the impact of COVID-19 on minoritized communities in intercollegiate sport / Yannick Kluch, Shaun Anderson & Tomika L. Ferguson.
CA CAMIA (Recommending faculty) AY2022-2023
Includes bibliographical references and index.
Keywords: Communication in sports -- Case studies; Sports -- Public relations -- Case studies; Sports -- Social aspects -- Case studies; Racism in sports -- Case studies; Sex discrimination in sports -- Case studies; Nationalism and sports -- Case studies; Homophobia and sports -- Case studies